Perrhenate Esters as Intermediates in Molecular Complexity-Increasing Reactions - Floreancig, Paul E. (Synlett, 2021)
Allylic alcohols form perrhenate esters upon reaction with Re2O7 or HOReO3. These species undergo nonstereospecific and nonregiospecific alcohol-transposition reactions through cationic intermediates. Sequencing these nonselective processes with reversible trapping by electrophiles results in cyclization reactions where regio- and stereocontrol are dictated by thermodynamics. The cationic intermediates can also be utilized as electrophiles in intra- or intermolecular dehydrative reactions with nucleophiles. These processes serve as the basis for applications in catalytic syntheses of a wide range of heterocyclic and carbocyclic structures that often show considerable increases in molecular complexity. This Account describes a sequence of events that started from a need to solve a problem for the completion of a natural product synthesis and evolved into a central element in the design of numerous new transformations that proceed under mild conditions from readily accessible substrates.1 Introduction2 Exploratory Studies3 Application to Spiroketal Synthesis4 Reactions with Epoxides as Trapping Agents5 Development of Dehydrative Cyclizations6 Bimolecular Reactions7 Spirocyclic Ether Formation8 Conclusions
Keywords: allylic alcohols; transposition; perrhenate esters; rhenium catalysis; stereoselectivity; molecular complexity